“Cristo vence, reina e impera”: catolicismo e modernidade em uma cidade inventada / "Christ wins, reigns, and rules": Catholicism and modernity in an invented city - Quadros, Eduardo Gusmão (PLURA, Revista de Estudos de Religião / PLURA, Journal for the Study of Religion, 2012)
<!--[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Tabela normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman","serif";} --> <!--[endif] --> Sob o impacto do regime implantado por Getúlio Vargas, foi gestado o projeto de fundação de uma nova capital para o Estado de Goiás, no Brasil. Assim nasceria Goiânia, projetada enquanto polo irradiador da modernidade naquela região central do país. Nesta configuração cultural, o moderno e o tradicional estiveram imbricados, recompondo o campo religioso. Estudamos neste artigo as representações construídas na transferência da capital, a nova espiritualidade e o modo como o catolicismo interagiu com a cultura política populista em formação. Abstract Under the impact of the political regime deployed by Getúlio Vargas, the project of a new capital for the State of Goiás, Brazil, was conceived. Thus Goiânia was born, intended to be a pole of radiating modernity in the country’s central region. In that cultural setting, the modern and the traditional were interwoven, recomposing the religious field. This article studies the representations and values built during the capital’s transfer, the new spirituality and the way Catholicism interacted with the forming populist political culture.